The Health Services (London : C. W. Publishing Ltd.)
1944-05 1944 1940s 23 pages 4 (d) Immunisation. Immunisation of children against diphtheria is a public service of a more recent date. Before the war it existed only in some areas, but in 1940 the Ministry of Health and the Department of Health for Scotland started a national immunisation campaign, and placed the toxoid free of charge at the disposal of all local authorities. By 1943 over 30 per cent. of the children between the ages of 1 and 15 in England and Wales and 73 per cent. of the school children in Scotland were immunised. But these figures are not yet considered satisfactory because it is now regarded as possible to conquer diphtheria altogether by means of universal immunisation. (2) The School Medical Service. It was found that under-nourished children were unable to take full advantage of school education, and the Education (Provision of Meals) Act, 1906, as a first step, empowered local authorities to provide meals for necessitous school children. The Education (Administrative Provisions) Act, 1907, for England and Wales, and a similar Act for Scotland in 1908, laid the basis for a school medical service. It made the care for the health and physical welfare of the school children a function of local authorities and introduced compulsory medical inspection. The present School Medical Service in England and Wales is based on the Education Act, 1921, which also empowered local authorities for the first time to provide milk free to necessitous school children. Very soon it became clear that medical inspection was not enough. One local authority after another made use of its power to provide certain kinds of medical treatment for those children whose parents were unable to procure it. Clinics were established for minor ailments ; and provision made for the removal of tonsils and adenoids, for dental and orthopaedic treatment, and for sight testing, with free glasses, where necessary. The standard and extent of these services vary considerably in different areas because they are based on permissive legislation only. Local authorities are not permitted, however, to provide a general practitioner service for the children, as this would infringe upon the privileges of independent medical practitioners. The new Education Bill makes it the duty of local authorities "to make arrangements for securing the provision of free medical treatment for pupils in attendance at any school or young people's college maintained by them as are necessary...." Although it does not include treatment at home, this section of the Bill provides for a considerable extension of the present service and compels all authorities to do what is now being done voluntarily by some. 15X/2/98/10